Wild Hogs in Florida: Ecology and Management - William M. Giuliano (EDIS)
WEC277, an 11-page illustrated fact sheet by William M. Giuliano, provides an overview of wild hogs in Florida — history, distribution, description, habitat relationships, general biology, problems, management, hunting, and other control measures. Published by the UF Department of Wildlife Ecology and Conservation, March 2010.